Cost-Effective Measurement Setup for Analyzing Signal Coverage in 4G/5G Mobile Networks - Polák, Ladislav; Baránek, Michal; Kufa, Jan; Šotner, Roman; Dluhá, Jitka (IEEE, 2025)
Long-term monitoring, measurement, and collection of key performance indicators (KPIs) for fourth and fifthgeneration (4G and 5G) networks under various transmission conditions are essential for optimizing performance and ensuring seamless connectivity in dense environments. In this paper, we present a cost-effective, portable measurement setup with an intuitive user interface, designed for efficient cost-efficient measurements in diverse environments. This setup was used for large-scale measurement studies of 4G (Long-Term Evolution - LTE) and 5G (Non-Standalone - NSA) mobile networks conducted in Brno, Czechia, enabling the exploration of indoor and outdoor network coverage across different radio frequency (RF) bands and environmental conditions. Using this equipment, nearly 1,500,000 samples were collected with a time resolution of 1 second. To support the reproducibility of our study, the dataset is publicly available for download. The results demonstrate varying performance of 4G and 5G mobile networks across different scenarios and show the significant impact of network load fluctuations based on the time of day.

Long-term monitoring, measurement, and collection of key performance indicators (KPIs) for fourth and fifthgeneration (4G and 5G) networks under various transmission conditions are essential for optimizing performance and ensuring seamless connectivity in dense environments. In this paper, we present a cost-effective, portable measurement setup with an intuitive user interface, designed for efficient cost-efficient measurements in diverse environments. This setup was used for large-scale measurement studies of 4G (Long-Term Evolution - LTE) and 5G (Non-Standalone - NSA) mobile networks conducted in Brno, Czechia, enabling the exploration of indoor and outdoor network coverage across different radio frequency (RF) bands and environmental conditions. Using this equipment, nearly 1,500,000 samples were collected with a time resolution of 1 second. To support the reproducibility of our study, the dataset is publicly available for download. The results demonstrate varying performance of 4G and 5G mobile networks across different scenarios and show the significant impact of network load fluctuations based on the time of day.
Cost-Effective Measurement Setup for Analyzing Signal Coverage in 4G/5G Mobile Networks
Keywords: 4G and 5G mobile networks; coverage mapping; data analysis; interpolation; key performance indicators (KPIs); 4G and 5G mobile networks; coverage mapping; data analysis; interpolation; key performance indicators (KPIs)